A modified decontamination and storage method for sputum from patients with tuberculosis [version 3; peer review: 1 approved, 2 approved with reservations] - Nguyen Thuy Thuong Thuong; Dang Thi Minh Ha; Timothy M. Walker; Nguyen Le Quang; Le Pham Tien Trieu; Guy Thwaites; Do Dang Anh Thu; Nguyen Huu Lan; Nguyen Hong Hanh (Wellcome Open Research)
Background Collecting and storing large number of sputum samples with a view to culturing these in the future requires an efficient initial handling method. We devised a modified sputum digestion and decontamination method that maximised storage capacity and Mycobacterium tuberculosis (M.tb) recovery from culture while minimising laboratory workload and risk of contamination. Methods We collected smear microscopy positive sputum samples from patients with pulmonary tuberculosis (TB). The sputum samples were split and processed using both the standard N-Acetyl-L-cysteine and sodium hydroxide (NALC-NaOH) method and our modified method before freezing and later culturing in BD BACTEC 960 Mycobacterium Growth Indicator Tubes (MGIT) system. We assessed the Time to Positivity (TPP) and Growth Unit (GU) data. Results We selected 22 sputum samples to compare two digestion and decontamination methods. The samples that underwent the modified method had longer TTP (p < 0.05) but similar GU in comparison to standard method. Overall, 1/22 samples failed to grow in MGIT after being processed by the modified method. We then applied the modified method to 348 sputum samples with Rifampicin resistance detected by GeneXpert MTB/RIF assay, which were frozen for between 1–25 months. The overall MGIT positive, negative, and contamination rate was 90.5%, 7.8%, and 1.7%, respectively. There was no significant difference in MGIT result when samples were grouped by duration of storage or positive smear grade. Conclusions Our modified method yielded acceptable M.tb recovery rate and low contamination risk while allowing us to collect and store thousands of sputum samples over a long period of time for future tests.